2013
DOI: 10.1111/ipd.12068
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of nursery school‐aged children who refuse fluoride varnish administration in a community setting: a Childsmile investigation

Abstract: Initial anxiety behaviour, previous varnish experience, and not using praise by the nursing staff predicted fluoride varnish application refusal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Further, the use of unreliable and poor quality information on websites about fluoride treatments may cause unfavorable outcomes as parents may use this information to determine whether to pursue fluoride treatments for their children. For example, hesitancy and refusal to use fluoride has been noted among caregivers as fluoride safety is a significant concern among this demographic; 15,25 and this phenomenon is similar to the opposition of some caregivers to vaccinations. A consequence is that many children do not benefit from the preventive effects of fluoride even though fluoride is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the use of unreliable and poor quality information on websites about fluoride treatments may cause unfavorable outcomes as parents may use this information to determine whether to pursue fluoride treatments for their children. For example, hesitancy and refusal to use fluoride has been noted among caregivers as fluoride safety is a significant concern among this demographic; 15,25 and this phenomenon is similar to the opposition of some caregivers to vaccinations. A consequence is that many children do not benefit from the preventive effects of fluoride even though fluoride is safe.…”
Section: Discussionmentioning
confidence: 99%
“…36 Unfortunately, DFA still creates significant barriers for children to have appropriate dental care. [37][38][39] Consequently, children with DFA are not as likely to benefit from the advances in the prevention, diagnosis, and treatment of dental caries now available. 40 During the last 50 years, DFA in children has been managed through the use of behaviour management strategies, such as 'tell-show-do', which is well-accepted, but has little evidence to support its effectiveness; or children have been referred to specialist services for pharmacological interventions.…”
Section: Greater Insights Into Children's Dental Fear and Anxietymentioning
confidence: 99%
“…Even though fluoride is effective and safe, recent data showed that 13% of parents refused fluoride treatments for their child during a preventive dental or medical visit((D'Hoore and Van Nieuwenhuysen, 1992)). Even more parents are fluoride hesitant, meaning that they may accept fluoride for their children but have unresolved concerns ((Humphris and Zhou, 2014)). These findings are of concern because fluoride is one of the few preventive treatments available for caries prevention( (Zhou, Forbes and Humphris, 2013)).…”
Section: Introductionmentioning
confidence: 99%